2013
DOI: 10.1186/1471-2393-13-233
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety symptoms and coping strategies in the perinatal period

Abstract: BackgroundThe aim of the present study was to explore the prospective relationship between anxiety symptoms and coping strategies during late pregnancy and early postpartum.MethodsParticipants completed the Hospital Anxiety Depression-Anxiety subscale and Carver’s Brief COPE at two time points, namely during the last trimester of pregnancy (N = 400) and at two months postpartum (N = 158).ResultsAntenatally, 18.8% of pregnant women presented severe anxiety symptoms while 20.2% of women presented severe anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
3
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(73 citation statements)
references
References 24 publications
4
63
3
3
Order By: Relevance
“…This is less instrumental in alleviating the stress and tends to increase the risk for anxiety symptoms. It seems that NC styles have direct independent effects on the severity of antenatal anxiety symptoms [15]. Contrary to our expectations, our findings revealed that the women's PC styles had no direct effects on antenatal anxiety symptoms, and these results are inconsistent with a previous study [15].…”
Section: Direct Effects Of Nc Stylescontrasting
confidence: 81%
See 2 more Smart Citations
“…This is less instrumental in alleviating the stress and tends to increase the risk for anxiety symptoms. It seems that NC styles have direct independent effects on the severity of antenatal anxiety symptoms [15]. Contrary to our expectations, our findings revealed that the women's PC styles had no direct effects on antenatal anxiety symptoms, and these results are inconsistent with a previous study [15].…”
Section: Direct Effects Of Nc Stylescontrasting
confidence: 81%
“…However, the findings of studies measuring the relationship between coping styles and anxiety symptoms are mixed. One study found that positive coping (PC) styles were negatively correlated with anxiety [15], while another study reported that PC styles have no effect on anxiety symptoms [16]. One study found that NC styles were positively correlated with anxiety symptoms [17], and another study reported NC styles to be associated with more positive feeling [18].…”
Section: Coping Styles As a Direct Effectmentioning
confidence: 95%
See 1 more Smart Citation
“…However, research that found this association identified prenatal depression as a significant predictor of LBW without gestational age control 6,27 . With regard to the probable diagnosis of generalized anxiety disorder, the frequency was elevated (19.3%), as already described in other studies with women during the gestational period 15,18 , which was also observed in a study carried out in the South of the country with pregnant women treated in 18 UBS, which found a very similar frequency (19.8%) to this study using the same screening tool 14 . The frequency of other MDs evaluated (bulimia nervosa, panic disorder and alcohol dependence) was lower than that found for depression and generalized anxiety; it was not associated to any mother's health variable, habits, socioeconomic status, schooling (mother and father), complications during pregnancy and NB conditions.…”
Section: Discussionsupporting
confidence: 90%
“…The high frequency of MD during pregnancy is supported by the literature in national studies with populations of low socioeconomic status 2,5 and attended by PHC 14 . In international research, the prevalence of psychiatric symptoms, particularly anxiety and depression, varies from 11.8% to 34.9% [15][16][17][18][19] , depending not only on the socioeconomic aspects of the period of time investigated, but also on the tool used in the detection.…”
Section: Discussionmentioning
confidence: 99%